Analisis Faktor Penyebab Pembengkakan Biaya Pada Proyek Konstruksi - Zalukhu, Alfred Eliasman; Zebua, Dermawan; Lase, Carsa Alim; Harefa, Felix Nitema; Zebua, Friski Dermawan; Loi , Anggerius (CV. SINAR HOWUHOWU, 2024)
Cost overrun is one of the problems that often occurs in the implementation of construction projects, which can have an impact on reducing project efficiency, productivity and profitability. This research aims to identify and analyze the main factors causing cost overruns on construction projects. The research methodology used includes questionnaire surveys and interviews with project stakeholders, such as contractors, consultants and project owners. The research results show that the main factors causing cost overruns are design changes during project implementation, inaccurate cost estimates, fluctuations in material prices, less effective project management, and late payments by the project owner. In addition, external factors such as poor weather conditions and government policies regarding construction also contribute to increased costs. This research suggests a proactive approach to project planning and control, including improving the quality of cost estimates, risk management, and effective communication between all parties involved. By understanding the factors that cause cost overruns, it is hoped that construction projects can be carried out more efficiently and in accordance with the planned budget.